Mauritius Addressing Inequality through More Equitable Labor Markets - World Bank Group (World Bank, Washington, DC, 2017)
Mauritius is often cited as one of the few African success stories, and with good reason. In the aftermath of independence (1968), this small island nation in the Indian Ocean seemed to be bound for economic failure because of its high poverty rate and numerous vulnerabilities, including high population growth, ethnic tensions, substantial unemployment, and an economy greatly dependent on the production of sugar for international markets. However, Mauritius was successful in diversifying the economy and accomplishing an unprecedented structural transformation.The Inclusiveness of Growth and Shared Prosperity report (World Bank 2015a) turned the spotlight on the expanding gap of inequality in household incomes that occurred between 2007 and 2012 and on the negative impact on poverty. The report estimates that the incidence of absolute poverty between 2007 and 2012 would have declined twice as quickly had growth been shared more widely and inequality not worsened. Building on these earlier findings, this study investigates the driving forces behind the growing income inequality and identifies policy levers that could mitigate and, in the long run, possibly reverse the upward trend.This study takes a comprehensive approach to the determinants of inequality by including the role of the choices of households and individuals, markets, and institutions. The report is structured as follows. Chapter one sets the stage by presenting stylized facts on the trends in household income inequality between 2001 and 2015, comparing these trends with trends in consumption inequality, and identifying the main culprit behind the rapidly rising inequality in household incomes, that is, household labor income. Chapter two supplies a set of descriptive trends of the two groups of factors, namely, household demographics and labor market forces, that contribute to changes in household laborincome and follows up with a decomposition exercise on changes in household labor income between 2001 and 2015.Because the analysis indicates that an unequal increase in female labor force participation and rising inequality in individual earnings are among the main contributors to the expanding inequality in household labor income, Chapter three takes a deep dive into the issue of gender inequality in the labor market. The chapter illustrates the gender gap in labor market participation, describes the differences in the activities of working women in the labor market relative to men, and concludes with a detailed analysis of gender gaps in wages separately in the public and private sectors. Chapter four resumes the main analysis of the drivers of increasing inequality in individual earnings. The chapter first presents stylized facts about overall inequality in wages and then separates out changes in inequality between and within groups defined by demographic characteristics. The chapter distinguishes the role of changes in prices (or wages) and the role of changes in the composition of the workforce in rising earnings inequality. The second part of the chapter is devoted to the analysis of the role of the main potential drivers of expanding earnings inequality. The possible candidates include the interaction of changes in labor supply and labor demand, giving rise to skills shortages or surpluses, and changes in labor market institutions, namely, remuneration orders (ROs). The chapter concludes with an analysis of an additional source of skills mismatches among the employed population, namely, education mismatches, and advances potential explanations for the coexistence of a substantial skills shortage, over education, particularly among youth, and a large share of highly educated youth among the unemployed.